In Situ Investigations of Simultaneous Two‐Layer Slot Die Coating of Component‐Graded Anodes for Improved High‐Energy Li‐Ion Batteries. Issue 5 (18th March 2020) - Diehm, Ralf; Kumberg, Jana; Dörrer, Christopher; Müller, Marcus; Bauer, Werner; Scharfer, Philip; Schabel, Wilhelm
Abstract : The use of thicker electrodes can contribute to a reduction in cell costs. However, the properties of the electrode must be kept in view to be able to meet the performance requirements. Herein, the possibility of simultaneous multilayer slot die coating is investigated to improve the electrode properties of medium‐ and high‐capacity anodes. The stable coating window of the two‐layer slot die coating process is investigated to produce property‐graded multilayer electrodes. Electrodes with different styrene–butadiene rubber (SBR) gradients are investigated with regard to adhesive force and electrochemical performance. An increase in the adhesive force of up to 43.5% and an increase in the discharge capacity is observed. Abstract : The pregrading of additives in Li‐ion battery electrodes during coating can provide significant benefits to their properties. Herein, it is shown that the graded two‐layer anodes can be produced by simultaneous multilayer coating with 2 mAh cm − 2 as well as high‐energy electrodes with 8 mAh cm − 2 . These graded anodes show a better adhesive force up to 43.5 % and a higher discharge capacity.